Liderança de mercado no setor de TICS Brasileiro: Estudos de caso da TOTVS e da positivo informática S/A - Bruno César Araújo; Rodrigo Abdalla Filgueiras de Sousa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The purpose of this paper is to examine the explaining factors of the market leadership of two Brazilian companies in specialized fields of the Information and Communication Technologies (ICT) sector. Whilst Totvs is a software house, dedicated to the Enterprise Resource Planning (ERP) segment since its foundation, Positivo is an assembly line of personal computers (PCs), which emerged as a spin-off from an economic group originally focused in educational services. Throughout the paper, case studies of both companies are performed, based on literature review, financial statements, press articles and in-depth interviews. In both cases, national idiosyncrasies have supported the emergence and consolidation of each company as a market leader. Notwithstanding economies of scale and scope are essential sources of competitive advantages in the ICT sector in general, both cases exhibit a combination of two other factors that counterbalance their initial disadvantages with respect to their international competitors. First, governmental support has been crucial, although using different approaches. Totvs' leading position has been reinforced by financial support from the Brazilian National Development Bank (BNDES), while Positivo has benefited from trade protectionism, under the "infant industry" argument. Second, both companies have achieved market leadership through the development of customized products and solutions to specific market segments that have not been properly addressed by world industry leaders, combining some technological capabilities with marketing capabilities. Recently, both companies have made efforts to enter the global market. Up to now, they both have focused on Latin America, in order to explore cultural, idiomatic and institutional similarities with Brazil.
Keywords: L86; L63; 330; Totvs; Positivo Informática; market leadership; Information and Communication Technology (ICT)